2018
DOI: 10.1016/j.bbi.2018.02.003
|View full text |Cite
|
Sign up to set email alerts
|

TNFα disrupts blood brain barrier integrity to maintain prolonged depressive-like behavior in mice

Abstract: Recovery from major depressive disorder is difficult, particularly in patients who are refractory to antidepressant treatments. To examine factors that regulate recovery, we developed a prolonged learned helplessness depression model in mice. After the induction of learned helplessness, mice were separated into groups that recovered or did not recover within 4 weeks. Comparisons were made between groups in hippocampal proteins, inflammatory cytokines, and blood brain barrier (BBB) permeability. Compared with m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
115
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 208 publications
(121 citation statements)
references
References 59 publications
4
115
0
2
Order By: Relevance
“…Similar can be observed when a TNFα inhibitor, etanercept, is administrated. These observations indicate that the stress-induced GSK3 activation contributes to the disruption of BBB integrity mediated by pro-inflammatory factors, particularly TNFα [70].…”
Section: Neuroinflammation In Depressionmentioning
confidence: 77%
See 2 more Smart Citations
“…Similar can be observed when a TNFα inhibitor, etanercept, is administrated. These observations indicate that the stress-induced GSK3 activation contributes to the disruption of BBB integrity mediated by pro-inflammatory factors, particularly TNFα [70].…”
Section: Neuroinflammation In Depressionmentioning
confidence: 77%
“…It has been demonstrated that non-ATP-competitive GSK3β inhibitors ameliorate depressive-like behavior in rodents. It has also been shown that prolonged learned helplessness is reversible and is maintained by abnormally active GSK3, whereas treatment with TDZD-8, non-ATP-competitive GSK3 inhibitor, reverses the impaired recovery from learned helplessness [70]. In turn, an ATP-competitive GSK3β inhibitor SB216763 has been found to increase anti-depressant responses in the forced swim test [71], whereas SAR502250 improved the stress-induced physical state in the chronic mild stress test in mice [72].…”
Section: Inhibitors Of Gsk3β In Depressionmentioning
confidence: 99%
See 1 more Smart Citation
“…We describe here a molecular framework in which cldn5-related epigenetic modifications and transcriptional changes in the NAc lead to stress resilience or vulnerability and depression. In rodents, depression-like behaviors have been associated with increased BBB permeability (7,8) while vascular dysfunction was not observed in those displaying stress resiliency (7,24). However, the cellular and molecular mechanisms involved in this process remained elusive.…”
Section: Discussionmentioning
confidence: 99%
“…We recently showed that chronic social stress induces blood-brain barrier (BBB) leakiness in the nucleus accumbens (NAc) of male mice, promoting passage of circulating proinflammatory mediators and the establishment of depression-like behaviors, including social avoidance, anhedonia, and helplessness (7). Stress-induced increase in BBB permeability is mediated by loss of tight junction protein claudin-5 (cldn5), a major cell adhesion molecule which forms a paracellular barrier between endothelial cells (7)(8)(9). We showed that CLDN5 expression is reduced in the NAc of depressed patients (7) in line with clinical studies reporting altered cerebrospinal fluid to serum ratio of peripheral markers in depression indicative of greater BBB permeability (10).…”
mentioning
confidence: 99%